'Photographed at the Royal Festival Hall' ... discursive constructions of dress, time and space in post-war British fashion media. Issue 1 (1st January 2016) - McDowell, Felice
This article discusses how the Royal Festival Hall (RFH) was featured as a location in editorial photo-spreads published in British fashion periodicals Vogue and Harper's Bazaar throughout 1952.1 It invites another way of looking at the RFH, an often-celebrated architectural icon of British post-war history and democratic achievement. This article focuses upon the spatiality of the fashion magazine and addresses how this particular object context can aid the historical analysis of fashion imagery, and representations of space. Here a history of fashion, dress codes, femininity, modern architecture and post-war public cultural space is garnered within the sequential layout of the fashion magazine page.